Santa-Anna Nery: um propagandista “voluntário” da Amazônia (1883-1901) - COELHO, Anna Carolina de Abreu (Universidade Federal do Pará, 2013)
To present paper analyzes under the historical point, of view the works Folclore Brasileiro and O País das Amazonas of the Amazonian intellectual Frederico de Saint-Anna Nery (1848-1901), looking for to argue the performance politics of the author during the end of the century XIX, approaching specifically its role in the spreading of a positive Amazonian identity wide abroad, which it was related to a bigger process of regional identities’ construction and of a process of Amazonian’s modernization, elaborated by the elites of the which the author was part of.